A pH-sensitive, renewable invisible orthodontic aligners coating manipulates antibacterial and in situ remineralization functions to combat enamel demineralization - Qin, Qi; Yuan, Wenhong; Zhang, Jiarui; Gao, Yang; Yu, Yanling (Frontiers in Bioengineering and Biotechnology, 2024)
During invisalign treatment, as salivary proteins or glycoproteins fill the space between the teeth and the aligners, they can easily adhere to the teeth, forming an acquired cellular film on which bacteria are highly susceptible to colonizing, which in turn leads to the development of enamel white staining lesions (WSLs), one of the major complications of orthodontic treatment. Inhibiting the activity of cariogenic bacteria while promoting the remineralization of demineralized enamel is the key to preventing and treating WSLs. Currently, the drug commonly used in clinical practice for the treatment of WSLs is silver diamine fluoride, which, although it has both antimicrobial and remineralizing effects, suffers from problems such as pulpal irritation and tooth discoloration. In this study, based on the principle of coordination chemistry, copper ions and plant polyphenol tannins were assembled on invisible orthodontic aligners to form a metal-phenol network coating (TA-Cu MPNs), and zwitterionic sulfonamethyldopamine was introduced for bionic mineralization to obtain the multifunctional coating TA-Cu MPNs@ZDS@CaP (TZC). The coating exhibits acidresponsive release of Ca 2+ and PO4 3-, and the decomposed CaP layer can be regenerated by a simple dipping method. The TZC coating strongly inhibits common cariogenic bacteria and their biofilms. In addition, the results of the in vitro mineralization experiment show that TZC-coated invisible orthodontic aligner treatment of demineralized enamel has significant remineralization effects. It is worth mentioning that the constructed coating has a durable antibacterial effect and can meet the service 2 cycle of invisible orthodontic aligners. This study provides theoretical and experimental bases for the prevention or treatment of WSLs in invisible orthodontic treatment.